TO STUDY THE EFFICACY AND SAFETY OF SITAGLIPTIN IN PATIENTS WITH TYPE-2 DIABETES MELLITUS - Dr. Deepak Kumar Patel; Dr. Neelesh Arya; Dr. J.L. Marko; Dr. Rajesh Singh Jagat; Dr. Prerna J Kerkatta; Dr. Ritesh Churihar; Dr. Tarun kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
DPP-4 is competitively inhibited by sitagliptin. This results in a plasma concentration of active GIP and GLP-1 that is elevated by more than two times, and it also produces a decrease in glucagon levels, an increase in insulin secretion, and improvements in fasting and postprandial hyperglycaemia. For combined oral therapy with DPP-4 inhibitors, four different types of oral antidiabetic medications can be used: alpha-glucosidase inhibitors, meglitinide, thiazolidinediones, and sulfonylureas.Objective of the study was To study the efficacy of Sitagliptin with oral hypoglycemic drugs(Sulfonylurea or Metformin) in reducing the fasting and postprandial blood glucose level in patients with type-2 diabetes mellitus.Methodology-The study was started after obtaining approval from the Institutional Ethics Committee, Gandhi Medical College Bhopal.The patient recruited for the study on the basis of inclusion and exclusion criteria and after obtaining written informed consent form from all the participating patients.enrolled patients coming to medicine OPD interval of 30th day and 60th day.Result: reduction in mean fasting blood sugar level at 30th day and 60th day , in Sitagliptin treated group (6.7% , 25.5%) , Sitagliptin + metformin treated group (12.8% , 29.2%) and Sitagliptin +metformin+Glimepiride Treated Group (19.5% , 40.2%) respectively. the reduction in mean post prandial blood sugar level at 30th day and 60th day , in Sitagliptin treated group (15.54% , 25.81%) , Sitagliptin + metformin treated group (17.79% , 32.57%) and Sitagliptin + metformin + Glimepiride treated group (25.18% , 39.13%) respectively.disscusion-The present study also demonstrated that both Sitagliptin + metformin and Sitagliptin + metformin + Glimepiride are almost equal efficacious and well tolerable than Sitagliptin alone in T2DM patients. However , Sitagliptin + metformin had a better safety profile as compared to Sitagliptin alone or Sitagliptin + metformin + Glimepiride Treated group.